Combined proton radiography and irradiation for high-precision preclinical studies in small animals - Schneider, Moritz; Bodenstein, Elisabeth; Bock, Johanna; Dietrich, Antje; Gantz, Sebastian; Heuchel, Lena; Krause, Mechthild; Lühr, Armin; von Neubeck, Cläre; Nexhipi, Sindi; Schürer, Michael; Tillner, Falk; et al. (Frontiers in Oncology, 2022)
Background and purpose: Proton therapy has become a popular treatment modality in the field of radiooncology due to higher spatial dose conformity compared to conventional radiotherapy, which holds the potential to spare normal tissue. Nevertheless, unresolved research questions, such as the much debated relative biological effectiveness (RBE) of protons, call for preclinical research, especially regarding in vivo studies. To mimic clinical workflows, high-precision small animal irradiation setups with image-guidance are needed. Material and Methods: A preclinical experimental setup for small animal brain irradiation using proton radiographies was established to perform planning, repositioning, and irradiation of mice. Image quality of proton radiographies was optimized regarding resolution, contrast-to-noise ratio (CNR), and minimal dose deposition in the animal. Subsequently, proof-of-concept histological analysis was conducted by staining for DNA double-strand breaks, which was then correlated to the applied dose. Results: The developed setup and workflow allow precise brain irradiation with a lateral target positioning accuracy of <0.26 mm for in vivo experiments at minimal imaging dose of <23 mGy per mouse. The custom-made software for image registration enables fast and precise animal positioning at the beam with low observer-variability. DNA damage staining validated successful positioning and irradiation. Conclusion: Proton radiography enables fast and effective high-precision lateral alignment of proton beam and target volume in mouse irradiation experiments with limited dose exposure. In the future, this will enable irradiation of larger animal cohorts as well as fractionated proton irradiation.